Tracing neurodevelopment and growth pattern in six-year-old children with idiopathic clubfoot: a national cohort study - Sung Tan Cho; Ha-Na Yoo; Simho Jeong; Ju Hee Kim; Eun Kyo Ha; Bo Eun Han; Wongthawat Liawrungrueang; Man Yong Han; Soonchul Lee (BMC Musculoskeletal Disorders)
Abstract Study design Population-based retrospective cohort study. Objectives The developmental impact of idiopathic clubfoot on children remains underexplored. This study investigates neurodevelopment and physical growth in children with idiopathic clubfoot up to age six. Methods This population-based retrospective cohort study was conducted in South Korea (2009–2019) using linked data from National Health Insurance Service. The cohort included children diagnosed with idiopathic clubfoot and 1:10 exact match of healthy control children. Neurodevelopmental assessments were conducted using the validated Korean Developmental Screening Test, which covers six domains: gross motor skills, fine motor skills, cognition, language, social skills, and self-regulation, for children aged 42–71 months. Secondary outcomes measured were height and body mass index (BMI) Z-score during the same period. Results The cohort comprised 484 children with idiopathic clubfoot and 4,840 matched healthy control children. Children with clubfoot had a higher rate of premature birth (7.44% vs. 3.66%, p < 0.0001) and lower birth weight (3.08 ± 0.59 kg vs. 3.20 ± 0.46 kg, p < 0.0001) compared to the healthy control children. In-depth evaluation of all six neurodevelopmental domains showed significant differences in children with clubfoot (overall aOR, 3.671; 95% CI, 2.463–5.471). Children with clubfoot showed a significant height delay (Z score, -1.63 below), but no BMI difference was noted. Conclusions Children with idiopathic clubfoot demonstrated increased risk of neurodevelopmental delays and reduced height compared to their peers. These findings underscore the importance of early recognition and ongoing monitoring by parents and pediatricians.